Paradigma dan Teori Ilmu Dakwah: Perspektif Sosiologis - Nur Syam (Institut Agama Islam Negeri Bengkulu, 2020)
As science, the science of da'wah has a paradigm and theory that enables the da'wah science to develop. There are five da'wah paradigms that can be further studied are paradigm factors, paradigm systems, interpretive paradigms, paradigm developmentalism and participatory paradigms. From this paradigm the theory can then be developed based on the theories of sociology. Among these theories, for example are the theories of da'wah phenomenology, da'wah social construction theory, da'wah dramaturgy theory, da'wah hermeneutics theory, da'wah communicative action theory, da'wah ethnometodology theory and so on. Through a sociological approach to the facts or reality of the da'wah, the science of da'wah will be able to develop more quickly. In the future, it should be considered about further development of the sociology of da'wah, psychology of da'wah, anthropology of da'wah, communication of da’wah etc., by utilizing the pattern of developing science based on the integration of science, namely the phenomenon of da'wah as an object of study and utilizing other sciences as an approach.